2010
DOI: 10.1097/aog.0b013e3181da8f09
|View full text |Cite
|
Sign up to set email alerts
|

Extreme Obesity in Pregnancy in the United Kingdom

Abstract: Nearly 1 in every 1,000 women giving birth in the United Kingdom is extremely obese. These women have increased risks of poor outcomes. Basic equipment was not universally available for the care of these women, and this, together with the increase in prevalence of obesity, has important implications for maternity service provision. There is an urgent need to address prepregnancy care and weight management programs to prevent this increase in prevalence, as well as to ensure that appropriate services are in pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
156
1
3

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 156 publications
(173 citation statements)
references
References 22 publications
13
156
1
3
Order By: Relevance
“…Obese women are more likely to require both caesarean section and instrumental delivery (11) (Table 1), paradoxically obese pregnant women are at an increased risk of the complications associated with operative delivery. These risks are further exaggerated in morbid obesity (12) (Table 2), where operative delivery poses challenges to both the anaesthetist and obstetrician. Given the high likelihood of operative delivery, even where vaginal delivery is attempted, the fact that 'emergency' caesarean section carries greater risks than 'elective' caesarean section, and the need for experienced members of staff if operative delivery is needed, one could argue that women with morbid obesity might be best delivered by elective caesarean section.…”
Section: Delivery Complicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Obese women are more likely to require both caesarean section and instrumental delivery (11) (Table 1), paradoxically obese pregnant women are at an increased risk of the complications associated with operative delivery. These risks are further exaggerated in morbid obesity (12) (Table 2), where operative delivery poses challenges to both the anaesthetist and obstetrician. Given the high likelihood of operative delivery, even where vaginal delivery is attempted, the fact that 'emergency' caesarean section carries greater risks than 'elective' caesarean section, and the need for experienced members of staff if operative delivery is needed, one could argue that women with morbid obesity might be best delivered by elective caesarean section.…”
Section: Delivery Complicationsmentioning
confidence: 99%
“…In extreme obesity (BMI> 50) the risk of adverse outcomes increases further. The United Kingdom Obstetric Surveillance system study of extreme obesity identified that BMI > 50 was associated with increased adjusted OR of a range of adverse outcomes, including gestational diabetes, thrombosis, preeclampsia, postpartum haemorrhage and intensive care unit admission (Table 2) (12) .…”
Section: Antenatal Pregnancy Complications Increased By Obesitymentioning
confidence: 99%
“…Recording BMI and being aware of associated risks of obesity remains important. 73,123 Recommendations l Health professionals should be aware of the associated risk of dying from severe obstetric morbidity in women with medical comorbidities. l Women with medical comorbidities should be identified and fully assessed for their risks in pregnancy.…”
Section: Box 6 Signs and Symptoms Of Sepsismentioning
confidence: 99%
“…Inadequate labor analgesia has consistently been identified as a factor associated with extension failure7, 20, 21, 22, 23, 24 and this relationship is also demonstrated in this cohort. Published data on pregnant women with ‘extreme obesity’ (BMI 50 kg/m 2 ) have estimated a prevalence of 1 : 1000 in the United Kingdom28 and 2.1 : 1000 in Australia 29. These cohort studies have identified a significantly higher rate of cesarean section, general anesthesia and problems or failure of neuraxial anesthesia in this group 28, 29.…”
Section: Discussionmentioning
confidence: 99%
“…Published data on pregnant women with ‘extreme obesity’ (BMI 50 kg/m 2 ) have estimated a prevalence of 1 : 1000 in the United Kingdom28 and 2.1 : 1000 in Australia 29. These cohort studies have identified a significantly higher rate of cesarean section, general anesthesia and problems or failure of neuraxial anesthesia in this group 28, 29. International maternity care guidelines make recommendations regarding the care of pregnant women with a BMI > 40 kg/m 2 , but do not differentiate between levels of BMI greater than 40 kg/m 2 25, 26, 30.…”
Section: Discussionmentioning
confidence: 99%